EKSISTENSI TAMAN BELAJAR ISTANA BELAJAR ANAK BANTEN (ISBANBAN) KOTA SERANG DALAM MENANAMKAN KARAKTER KREATIF TERHADAP PESERTA BELAJAR DI KAMPUNG CIMOYAN KELURAHAN SEPANG KECAMATAN TAKTAKAN KOTA SERANG - Ray Ammanda; Wika Hardika Legiani; Ronni Juwandi (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this research was to determine the existence of the Taman Belajar Istana Belajar Anak Banten (ISBANBAN) Serang City in instilling creative character in the learning participants. This research was conducted in Cimoyan, Sepang, Taktakan, Serang City. This research uses a qualitative approach with a descriptive method. Data was collected through interviews, observation, and documentation. The results of the study showed that the existence of the Taman Belajar Isbanban can be seen from the existence of a learning place both physically and in the learning process that is still on going from 2018 until now. The innovation from the Taman Belajar Isbanban can be seen from 3 supporting factors in implementing innovation, including: individual factors, structural factors, and cultural factors. For individual factors, that is awarding of the best volunteers, the consistency of making RPP (Rencana Pelaksanaan Pembelajaran) and learning video documentation. The last, there is harmony between volunteers. Furthermore, from structural factors, administrative patterns and communication between structures in the Serang City Isbanban run complement each other according to the assignment of tasks during the implementation of learning, and providing family incentives such as eating together. Then from the cultural factor, isbanban volunteers in Serang city are also supported by the upgrading of volunteers carried out by the management, as well as the involvement of isbanban collaboration with outside supporting parties.Keyword: Existence, Taman Belajar, Creative Character